Hubungan Kadar HbA1c dengan Kadar Ureum dan Kreatinin pada Penderita Penyakit Diabetes Melitus Tipe 2 - Hertanti, Nety Widya; Indanah, Indanah (Jaringan Laboratorium Medis, 2025)
Diabetes mellitus (DM) is a condition characterized by elevated blood sugar levels (hyperglycemia), where if blood sugar levels do not function normally, it will result in complications for the body. One of the indicators of diabetes mellitus is the HbA1c test. poor glycemic control triggers the onset of nephropathic complications, which can be diagnosed with urea and creatinine tests. This study aims to understand the relationship between HbA1c, urea, and creatinine levels in individuals with type 2 diabetes. This study uses a quantitative correlation analysis design with a cross-sectional design. A total of 48 respondents were selected using the random sampling method. The results of the measurement of the variables studied showed a high HbA1c level of (60.4%), a high urea level of (4.2%), and a high creatinine level of (39.6%). The Pearson correlation test shows that there is a positive  relationship between HbA1c levels and urea levels, with a p-value of 0.006, which is less than 0.05 (0.006 0.05). Meanwhile, the relationship between HbA1c and creatinine shows that there is no significant relationship between HbA1c levels and creatinine levels, with a p-value of 0.352.